2007
DOI: 10.1007/s00586-007-0381-3
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent scar contracture scoliosis caused by back scalding during the infantile period

Abstract: The study design was a retrospective study in adolescent scar contracture scoliosis caused by back scalding during the infantile period. The objective of the study was to investigate the pathogenesis, clinical manifestation and treatment of adolescent scar contracture scoliosis caused by back scalding during the infantile period. This condition seldom occurs and is not reported in current English literature. One patient was first treated with skin expansion, back scar excision and skin flap transfer, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
9
0
4
Order By: Relevance
“…Schneider e Qu 8 ) highlighted that the asymmetric burns in the trunk, hips and shoulder girdle can lead children to favor the affected side, that is, an inclination towards the burned area. Quiu et al 27 ) , also reported that wound contracture, in the trunk can lead to imbalance in the lateral-spine. In this context, most children and adolescents had their trunks affected by the burn and in accordance with Quiu et al 27 ) , it was possible to verify the lateral deviation in both groups, as well as the individual analysis made it possible to notice the asymmetry of the injury, however, it was not possible to notice the detection of any pattern to explain the difference in weight transfer between the groups.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Schneider e Qu 8 ) highlighted that the asymmetric burns in the trunk, hips and shoulder girdle can lead children to favor the affected side, that is, an inclination towards the burned area. Quiu et al 27 ) , also reported that wound contracture, in the trunk can lead to imbalance in the lateral-spine. In this context, most children and adolescents had their trunks affected by the burn and in accordance with Quiu et al 27 ) , it was possible to verify the lateral deviation in both groups, as well as the individual analysis made it possible to notice the asymmetry of the injury, however, it was not possible to notice the detection of any pattern to explain the difference in weight transfer between the groups.…”
Section: Discussionmentioning
confidence: 96%
“…Quiu et al 27 ) , also reported that wound contracture, in the trunk can lead to imbalance in the lateral-spine. In this context, most children and adolescents had their trunks affected by the burn and in accordance with Quiu et al 27 ) , it was possible to verify the lateral deviation in both groups, as well as the individual analysis made it possible to notice the asymmetry of the injury, however, it was not possible to notice the detection of any pattern to explain the difference in weight transfer between the groups. For the analysis of the lower limbs no significant difference was observed, as well as in the analysis of the difference of length of the lower limbs (A7), the average values were close to zero.…”
Section: Discussionmentioning
confidence: 96%
“…50 Similarly, childhood burns of the anterior neck, shoulders, and chest wall may produce a rounding of the shoulders and sunken chest. Likewise, burn scar shortening and protective posturing can result in kyphosis.…”
Section: Heterotopic Ossificationmentioning
confidence: 99%
“…The new nomenclature proposed by Qiu [4] was introduced to avoid the confusion between idiopathic scoliosis, congenital scoliosis and many other types of scoliosis, such as Duchenne muscular dystrophy, thoracotomy, multicore myopathy with paraspinal contractures, contractures and growth disturbances in the hip and pelvis, especially radiation to the juxtaspinal and fractures to the bony spinal column along with continued exposure to physiological stresses.…”
Section: Diagnosis and Incidencementioning
confidence: 99%
“…Its incidence was reported to be 0.31 % because there were The left thoracolumbar curve was 122°with an apex at T11, and kyphosis was 100°, and b 1.5 months after Halo-bilateral femoral traction, the AP X-rays showed that coronal major curve was 72°3 only four cases of adolescent scar contracture scoliosis in 1,300 patients operated [4]. The pathogenesis of scar contracture scoliosis correlates more closely with the socalled postradiation spinal deformity [1] after radiation to the juxtaspinal and pleural scoliosis following extensive pleural scarring [3] due to chronic or acute infection.…”
Section: Diagnosis and Incidencementioning
confidence: 99%